The history and social significance of motion pictures in South Africa, 1895-1940 - Gutsche, Thelma (Department of Political Studies, 2016)
The nineteenth century culminated in a wealth of scientific inventiveness which resulted in a complete and fundamental change in social life within the following fifty years. The more widespread use of telegraphy, the expansion of the telephone service, the increased application of electricity and the invention of the motor car, the sudden appearance and phenomenal development of the cinema, and finally the invention and speedy public utilisation of the aeroplane and the wireless have combined to obliterate (except in trivial instances such as its "naughtiness") appreciation of the atmosphere of the period in which motion pictures first appeared. In South Africa, a remarkable degree of self-reliance was practiced by the populations of comparatively isolated towns during the nineties. Despite the slowness of communication, the laboriousness of travel and the leisurely tempo of life in general, despite every adverse circumstance, people construed out or their immediate surroundings a cultural life far more enterprising than that produced by favourable modern conditions.